Optimization of Data-Driven School Financial Management to Improve Operational Budget Efficiency at Private Schools under the Pancasila Education Foundation, Langkat Regency - Khairani, Khairani; Tamba, Riris Debora (Amkop Management Accounting Review (AMAR), 2025)
This study aims to analyze the effectiveness of implementing the e-RKAS (Electronic School Activity and Budget Plan) system in improving financial management efficiency at schools under the Pancasila Education Foundation in Sawit Seberang, Langkat Regency. The research uses a quantitative approach with a pre-experimental one-group pretest–posttest design, comparing conditions before and after the implementation of the e-RKAS system. The sample consisted of 25 respondents, including principals, treasurers, operators, and teachers. Measurements were carried out using four main indicators: budget realization ratio, number of budget deviations, timeliness of reporting, and user satisfaction. Data were analyzed using the Paired Sample T-Test in SPSS version 26. The findings indicate a significant improvement across all indicators after the implementation of e-RKAS (p < 0.05). The e-RKAS system effectively enhanced budget realization accuracy, reduced deviations, accelerated financial reporting, and improved user satisfaction. These results confirm that digitalizing school financial management strengthens efficiency, transparency, and accountability in managing education funds. This study offers important implications for the development of digital transformation policies in the education sector, particularly in encouraging the adoption of e-RKAS in private schools and in regions with limited resources.